Food system innovations for healthier diets in low and middle-income countries - de Brauw, Alan; Berg, Marrit van den; Brouwer, Inge D.; Snoek, Harriette; Vignola, Raffaele; Melesse, Mequanint B.; Lochetti, Gaia; Wagenberg, Coen van; Lundy, Mark M.; Maitre d’Hôtel, Elodie; Ruben, Ruerd (International Food Policy Research Institute, 2019)
Malnutrition in all its forms is a major challenge everywhere in the world, and particularly in low and middle income countries. To reduce malnutrition, innovations in food systems are needed to both provide sufficient options for consumers to obtain diets with adequate nutritional value, and to help consumers make conscious and unconscious choices to choose healthier diets. A potential solution to this challenge is food systems innovations designed to lead to healthier diets. In this paper, we lay out a multidisciplinary framework for both identifying and analyzing innovations in food systems that can lead to improvements in the choices available to consumers and their diets from a health perspective. The framework identifies entry points for the design of potential food systems innovations, highlighting potential synergies, feedback, and tradeoffs within the food system. The paper concludes by providing examples of potential innovations and describes future research that can be developed to support the role of food systems in providing healthier diets.